REMITANSI TENAGA KERJA INDONESIA: DAMPAKNYA TERHADAP INFLASI DAN KONTRIBUSINYA TERHADAP PENINGKATAN KUALITAS HIDUP MASYARAKAT - Eny Haryati (EKUITAS (Jurnal Ekonomi dan Keuangan), 2009)
Indonesian manpower (IM) is a term used to refer to the Indonesian migrants who work overseas. Although the exact number of the IM is not well recorded by the government of the Republic of Indonesia, the amount of the remittance the IM send home to their family is found to be quite significant. In 2005, the Minister of Manpower and Transmigration of the Republic of Indonesia declared that the amount of the IM’s remittance reached US$ 2.9 billion, which was much higher than the government’s expected amount (US$ 1.9 billion). This study found out that (1) the IM’s remittance affected the amount of the money spreading in the home district where the IM came from so that it enhanced the purchasing power of the people in the district towards the consumptive goods and services which, in turn, triggered the elevation of the prices of goods and services; (2) the IM’s remittance stimulated the traders or merchants to determine the goods and services pricing which was commonly called the expected inflation; (3) most of the remittance was spent for consumptive goods and services and only a little amount of it was spent for investment; and (4) the IM’s remittance was a factor that positively affected the increase of the human development index (HDI) in the IM’s home district. To effectively increase the effect of the remittance towards the HDI in the IW’s home district, a governmental policy that was oriented towards the development of the IM’s family potentials and attempted to change people’s behavior